ELVIRA GARCÍA Y GARCÍA AND PERUVIAN EDUCATION - Marrou Roldán, Aurora Soledad (2014)
Pedagogical orientation Elvira Garcia and Garcia is not without criticism of the education of the time, which just gives full force today. This is inferred from written as: The education child, text with an evident intention reformist and not a claim for gender ignores. In fact, Garcia and Garcia gender seeks to contribute by their actions in building the intellectual basis, with deep human, that allows the boarders face expectant and historical role for which necessarily calls like women so understood as a pioneer in this field. The reflection on their thinking aims to highlight the need to rethink the role of women, the teacher, the relationship with the family in general and children in particular, to rethink education from there today, inferring its complex possibilities and making its permanent latent crisis.